1997
DOI: 10.1007/bf02873675
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E status in protein energy malnutrition

Abstract: Serum vitamin E and cholesterol concentrations were measured in 50 children with protein energy malnutrition (PEM) and results were compared with a group of 50 normal controls. Mean serum vitamin E concentration as well as vitamin E/cholesterol ratio were found to be reduced in children with PEM while their mean serum cholesterol level was not significantly different from the control group. Data suggest that the reduced levels of serum vitamin E in PEM may be a result of malnutrition per se.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Mean serum albumin and α-tocopherol levels also decrease significantly in the different classes of PEM patients. Our findings are consistent with the report of Abrol et al [11], who reported gradual decrease in serum levels of αtocopherol with the severity of malnutrition. This could be attributed to the disturbed low density lipoprotein (LDL) metabolism since α-tocopherol is known to be delivered to cells via the high affinity receptors for LDL.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Mean serum albumin and α-tocopherol levels also decrease significantly in the different classes of PEM patients. Our findings are consistent with the report of Abrol et al [11], who reported gradual decrease in serum levels of αtocopherol with the severity of malnutrition. This could be attributed to the disturbed low density lipoprotein (LDL) metabolism since α-tocopherol is known to be delivered to cells via the high affinity receptors for LDL.…”
Section: Discussionsupporting
confidence: 94%
“…Vitamin E (tocopherol) is a powerful lipophilic antioxidant which protects unsaturated lipids against peroxidation and erythrocyte membrane from oxidant stress and is associated with drug metabolism; haem biosynthesis and neuromuscular function [9] and it had also been reported to enhance immune responses and is effective against bacterial infections [10]. The concentration of vitamin E in the plasma depends on dietary intake and plasma lipid concentration [11].…”
Section: Introductionmentioning
confidence: 99%
“…The serum vitamin E status was found to be extremely lower in patients. The reduced concentration of vitamin E may be due to enhanced generation of free radicals, that causes inflammation, leads to vascular leakage, which thereby results in oedema in Kwashiorkor [10,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Along with proteins, energy, and trace elements, vitamin E deficiency is more common and it adds to mortality and morbidity of the underlying disease. The deficiency of vitamin E has been suggested to be a causative factor in the anaemia of Kwashiorkor [14,15]. It is well known fact that concentrations of plasma vitamin E of above 500 μgm/dl is indicator of adequate vitamin E nutrition and depleted levels are always associated with fragility of erythrocytes [14].…”
Section: Introductionmentioning
confidence: 99%
“…A pathological im6alance has been termed as oxidative stress which may make an important contribution to disease pathology (37). Alternatively, increased oxidative stess may also be a result of the disease itself (38,39). Studies have shown that auto-oxidation of Hcy produces ROSs, specially in the presence of free transition metal ions (tM **).…”
Section: Hyperhomocysteinemia-oxidative Stressatherosclerosis-cardiovmentioning
confidence: 99%